Strategi akomodasi komunikasi pendidikan seks remaja dalam keluarga kawin campur antar ras - Clara; Murtiningsih, Bherta Sri Eko (Jurnal Studi Komunikasi, 2022)
The role of parents is very important in communicating sex education to children. However, in this study, the researchers focused on communication between families of different cultures, namely parents from Indonesia and the Netherlands in providing sex education to adolescents. Every culture has a different view of sex education. It can be seen that Indonesian culture still considers sex education taboo, so few parents discuss sex education for teenagers. At the same time, in the Netherlands, there are programs on sex education so that children can get it and avoid its unhealthy effects. The study aimed to determine: 1) family communication patterns in sex education by parents to adolescents in families of different cultures; 2) knowing the communication barriers faced and the role of family communication in discussing sex education in families of different cultures. The theory used in this research is Communication Accommodation. This study uses a qualitative approach with a case study method. The data collection technique used is in-depth interviews. The findings show that the communication pattern shown by families with Dutch Sundanese culture is a balanced split pattern and the Dutch-Balinese family shows an equality split pattern of communication. The communication pattern that takes place is driven by intercultural relationships that are open and mutually respectful. The obstacles found were differences in mindsets and ways of communicating in discussing sexual problems in children and the three families of participants showed using a convergence strategy in communicating and interacting with family members, namely by adjusting their mindset, intonation, gesture, language, behaviour or Actions in carrying out family communication to communicate can be successful.